Entrepreneurship Mentoring as an Effort to Increase Business Income - Christina Heti Tri Rahmawati; Theodorus Sutadi; Trisnawati Rahayu (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This community service raises the problems faced by the rempeyek business named SW-21. Based on interviews, there are several problems experienced by the SW-21 owner, namely good financial management and business legality management. The solution provided from the community service activity to overcome these problems is to provide entrepreneurial assistance on the importance of financial management and business legality management. The results of the community service activity for the SW-21 MSME include: (1) the SW-21 MSME owner has financial literacy in the moderate category regarding financial service products for investment, saving, borrowing and insurance; (2) the SW-21 MSME is able to manage finances by making good financial records; (3) the SW-21 MSME has business legality; (4) the SW-21 MSME has a business modal canvas to develop the business; and (5) the SW-21 MSME has a business signboard and uses social media Whatsapp and Instagram as well as the online food delivery service platform through Shopee Food to increase product marketing. The implication of this community service activity is that it is hoped that the entrepreneurship assistance will make it easier for SW-21 MSMEs to manage patents, develop their businesses, and increase their income and business sustainability.